Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3389/fnhum.2013.00018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the combination of P3-based GKT and reality monitoring on deceptive classification

Abstract: The study aimed to investigate whether a combination of the P3-based Guilty Knowledge Test (GKT) and reality monitoring (RM) distinguished between individuals who are guilty, witnesses, or informed, and using both tests provided more accurate information than did the use of either measure alone. Participants consisted of 45 males that were randomly and evenly assigned to three groups (i.e., guilty, witness, and informed). The guilty group conducted a mock crime where they intentionally crashed their vehicle in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…Several studies focused on event-related brain potentials and demonstrated that ERP components were susceptible to contextual factors such as the personal involvement in a misdeed during encoding (Jang et al, 2013 ) or the nature of memory tested in the CIT (episodic vs. semantic, Ganis and Schendan, 2013 ). Furthermore, it was found that depth of encoding modulated electrodermal responses to crime-related details but did not affect P300 responses in the CIT (Gamer and Berti, 2012 ).…”
Section: Current Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies focused on event-related brain potentials and demonstrated that ERP components were susceptible to contextual factors such as the personal involvement in a misdeed during encoding (Jang et al, 2013 ) or the nature of memory tested in the CIT (episodic vs. semantic, Ganis and Schendan, 2013 ). Furthermore, it was found that depth of encoding modulated electrodermal responses to crime-related details but did not affect P300 responses in the CIT (Gamer and Berti, 2012 ).…”
Section: Current Researchmentioning
confidence: 99%
“…These studies collectively demonstrate that a number of behavioral and physiological variables are susceptible to concealed information and therefore allow for detecting individuals with crime-related knowledge. Moreover, several of these studies reported enhanced classification accuracy when combining different indices of concealed information (Ambach et al, 2012 ; Seymour et al, 2012 ; Jang et al, 2013 ).…”
Section: Current Researchmentioning
confidence: 99%
“…Specifically, it has been proposed that the left ATL is preferentially involved in processing names of people and the right ATL is preferentially involved in processing familiar faces ( Damasio et al 2004 ; Snowden et al 2004 ; Gainotti 2013 ). There is also an ongoing debate as to whether the ATLs preferentially process semantic knowledge for familiar people ( Simmons et al 2010 ; Von Der Heide, Skipper, Olson 2013 ), which could be related to their high intrinsic social relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies compared the P300-based CIT effect for culprits of a mock-crime with witnesses or participants who were informed about the mock-crime (Jang et al, 2013;Rosenfeld, Ozsan, et al, 2017;Winograd & Rosenfeld, 2014). Culprits performed or imagined performing an immoral behavior, like stealing a ring or intentionally hitting another person in a car crash.…”
Section: Erp Studies With Different Moral Contextsmentioning
confidence: 99%